Prevalence of Dyslipidemia in Patients Diagnosed with Ischemic Heart Disease in Najaf - Sahib, Amjed Mohammed (Medical Science Journal for Advance Research, 2026)
Background: Ischemic heart disease (IHD) remains a major cause of morbidity and mortality worldwide and is strongly associated with lipid metabolism abnormalities. This study aimed to evaluate lipid profile alterations and determine the prevalence of dyslipidemia among patients diagnosed with IHD in Najaf, Iraq. Methods: A cross-sectional case–control study was conducted at Al-Sadr Teaching Hospital from October 2024 to January 2025. The study included 60 participants: 40 patients diagnosed with IHD by MRI and 20 apparently healthy controls. Serum total cholesterol (TC), triglycerides (TG), high-density lipoprotein (HDL), low- density lipoprotein (LDL), and very-low-density lipoprotein (VLDL) were measured using enzymatic colorimetric methods. Statistical analysis was performed using SPSS version 22, and p ≤ 0.05 was considered statistically significant. Results: Patients with IHD exhibited significantly elevated TC (222.35 ± 48.62 mg/dL), TG (246.75 ± 76.15 mg/dL), and VLDL (59.20 ± 29.64 mg/dL) compared with controls (158.95 ± 26.72, 108.65 ± 24.52, and 21.72 ± 4.91 mg/dL, respectively; p < 0.001). HDL levels were significantly lower in patients (34.62 ± 8.03 mg/dL) than in controls (45.45 ± 5.39 mg/dL; p < 0.001). LDL levels were higher in patients, but did not reach statistical significance (p = 0.1). ROC analysis demonstrated strong diagnostic performance for TG (AUC = 0.944), indicating high discriminative ability. Implications: The findings highlight the high prevalence of dyslipidemia among IHD patients and emphasize the importance of routine lipid profile assessment for early detection and cardiovascular risk stratification. Discussion: The observed dyslipidemic pattern—characterized by elevated TC, TG, and VLDL levels with reduced HDL—supports the established role of lipid abnormalities in atherosclerosis progression. The strong diagnostic value of triglycerides suggests that TG may serve as a practical and accessible biomarker in clinical evaluation of IHD patients. Conclusion: Patients with ischemic heart disease in Najaf demonstrate significant lipid profile disturbances. Triglycerides, in particular, show excellent diagnostic accuracy and may serve as a supportive biomarker in IHD assessment. Larger prospective studies are recommended to confirm these findings.